Anomalous placement of introns in a member of the intermediate filament multigene family: an evolutionary conundrum. - Lewis, S A (1986)
The origin of introns and their role (if any) in gene expression, in the evolution of the genome, and in the generation of new expressed sequences are issues that are understood poorly, if at all. Multigene families provide a favorable opportunity for examining the evolutionary history of introns because it is possible to identify changes in intron placement and content since the divergence of family members from a common ancestral sequence. Here we report the complete sequence of the gene encoding the 68-kilodalton (kDa) neurofilament protein; the gene is a member of the intermediate filament multigene family that diverged over 600 million years ago. Five other members of this family (desmin, vimentin, glial fibrillary acidic protein, and type I and type II keratins) are encoded by genes with six or more introns at homologous positions. To our surprise, the number and placement of introns in the 68-kDa neurofilament protein gene were completely anomalous, with only three introns, none of which corresponded in position to introns in any characterized intermediate filament gene. This finding was all the more unexpected because comparative amino acid sequence data suggest a closer relationship of the 68-kDa neurofilament protein to desmin, vimentin, and glial fibrillary acidic protein than between any of these three proteins and the keratins. It appears likely that an mRNA-mediated transposition event was involved in the evolution of the 68-kDa neurofilament protein gene and that subsequent events led to the acquisition of at least two of the three introns present in the contemporary sequence.